RECOGNITION OF CALLIGRAPHY WRITING PATTERNS USING THE ZERNIKE MOMENT METHOD AND SUPPORT VECTOR MACHINE - Mhd. Furqan; Sriani Sriani; Riswanda Ichsan Himawan Hasibuan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: One of the great arts of Islam that is very attached to Muslims is the art of calligraphy. The art of writing in calligraphy is of many types because the art of calligraphy is generally handwritten by someone called khatat and each khatat has its own technique for writing calligraphy. There fore there are many variations of calligraphy writing, even with the same type of writing. With so many variations of the type of calligraphy writing, technological innovation is needed to recognize variations of each type of calligraphy. Types of calligraphy diwani, diwaji jali, naskhi and tsuluts are the objects of this study. The Zernike Moment method is a feature extraction method that has the advantage of being invariant to rotate (resistant to rotation) and can help identify calligraphy types well based on their features. And the Support Vector Machine method is a good method for identifying calligraphy types by finding the best hyperplane. The combination of the Zernike Moment method and the Support Vector Machine is proven to produce good accuracy in recognizing calligraphy types based on their features, the accuracy obtained in identifying calligraphy types is 95%.Â Keywords: Pattern Recognition, Zernike Moment, Support Vector Machine, Calligraphy Abstrak: Salah satu seni besar Islam yang sangat melekat di kalangan umat Islam adalah seni kaligrafi. Seni menulis kaligrafi banyak macamnya karena seni kaligrafi umumnya ditulis tangan oleh seseorang yang disebut khatat dan setiap khatat mempunyai teknik penulisan kaligrafi tersendiri. Oleh karena itu terdapat banyak variasi penulisan kaligrafi, bahkan dengan jenis tulisan yang sama. Dengan banyaknya variasi jenis tulisan kaligrafi, diperlukan inovasi teknologi untuk mengenali variasi setiap jenis kaligrafi. Jenis kaligrafi diwani, diwaji jali, naskhi dan tsuluts menjadi objek penelitian ini. Metode Zernike Moment merupakan salah satu metode ekstraksi ciri yang mempunyai kelebihan yaitu bersifat invarian terhadap rotasi (tahan terhadap rotasi) dan dapat membantu mengidentifikasi jenis-jenis kaligrafi dengan baik berdasarkan ciri-cirinya. Dan metode Support Vector Machine merupakan metode yang baik untuk mengidentifikasi jenis kaligrafi dengan mencari hyperplane terbaik. Kombinasi metode Zernike Moment dan Support Vector Machine terbukti menghasilkan akurasi yang baik dalam mengenali jenis kaligrafi berdasarkan ciri-cirinya, akurasi yang didapat dalam mengidentifikasi jenis kaligrafi adalah 95%.Â Kata kunci: Pengenalan Pola, Momen Zernike, Mesin Vektor Pendukung, Kaligrafi